Edukasi Pencegahan Kekerasan Seksual pada Peserta Didik SMA Plus Ar Raudah Purwakarta - Meisya Edlina Mardani; Nadya Yulianty S; Enan Kusnandar; Dede Supendi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Sexual violence is an act that humiliates, insults, harasses, attacks a person's body or reproductive function, due to unequal power or position relations. There are various types of violence such as physical violence, psychological violence, sexual violence, trafficking, etc. The impact of violence includes physical, emotional and psychological trauma for the victim. Preventing sexual violence is a shared responsibility and requires cooperation from various parties, including government, educational institutions, communities and individuals. Cases of sexual violence among students are a major problem, especially when it occurs in the school, family and other environments. It is not uncommon for cases of sexual violence to occur that cause trauma for the victim. The problem that occurred at SMA PLUS AR-RAUDHAH was related to the lack of knowledge of students regarding the prevention of sexual violence, in addition to the lack of assistance and knowledge taught by educators to students regarding the prevention of sexual violence with 121 participants. The aim of carrying out this service activity is to form students' understanding, especially SMA PLUS AR-RAUDHAH students, regarding sexual violence, its impact and prevention, so that it is hoped that students can avoid sexual violence. This service method is carried out through several stages, namely the preparation stage and the implementation stage and this activity uses the lecture method. The results obtained from this service are that students' understanding of the types, impact of sexual violence and prevention of sexual violence personally increases.